17th AIAA/CEAS Aeroacoustics Conference (32nd AIAA Aeroacoustics Conference) 2011
DOI: 10.2514/6.2011-2843
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Cylinder and Idealized Side Mirror Far-Field Noise Predictions Using DES and An Efficient Implementation of FW-H Equation

Abstract: A computationally e¢ cient Ffowcs Williams-Hawkings acoustic analogy model has been incorporated in a modern CFD code. This methodology is based on the fact that the aerodynamic noise prediction can be performed in parallel with the aerodynamic computation. Near-…eld aerodynamics have been computed using unsteady Navier-Stokes equations with DES turbulence modeling. The sound propagation in far…eld is solved based on a e¢ cient implementation of the Farassat' s formulation 1A of the Ffowcs Williams-Hawkings eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The SPL spectra predicted by the structured grid at M4 over predicts the SPL intensity compared to measured data, while the poly-hex core grid agrees well with the intensity in measured spectra. 24 At the high-frequency range, the prediction from both the grids give a maximum difference of 8-9 dB from experimental data, and this difference in the predicted spectra is consistent with the other numerical results published by Ask and Davidson 23,24 and Caraeni et al 19 At M10 and M11, the predicted SPL is in good agreement with the measured data throughout the SPL spectra, as shown in Fig. 12.…”
Section: Tablesupporting
confidence: 89%
See 1 more Smart Citation
“…The SPL spectra predicted by the structured grid at M4 over predicts the SPL intensity compared to measured data, while the poly-hex core grid agrees well with the intensity in measured spectra. 24 At the high-frequency range, the prediction from both the grids give a maximum difference of 8-9 dB from experimental data, and this difference in the predicted spectra is consistent with the other numerical results published by Ask and Davidson 23,24 and Caraeni et al 19 At M10 and M11, the predicted SPL is in good agreement with the measured data throughout the SPL spectra, as shown in Fig. 12.…”
Section: Tablesupporting
confidence: 89%
“…From a numerical perspective, several turbulence modelling approaches have been carried out by researchers for hydrodynamic pressure fluctuations on both the mirror and plate. 5,[14][15][16][17][18][19][20][21][22] The efforts based on Unsteady Reynolds Averaged Navier Stokes (URANS) and Ffowcs Williams-Hawkings (FW-H) approaches 12,13 have shown to yield a difference of up to 7dB in Sound Pressure Levels (SPL) recorded with microphones positioned around the mirror for frequencies ranging from 200 -300 Hz, but beyond 300 Hz they show considerable disparity with experimental data and the pressure fluctuations predicted at sensors located on the mirror and the plate flatten out after 200 Hz indicating the limitation of the RANS models in resolving the intricate details of the flow which are necessary to capture high-frequency modes. Ask and Davidson 16,23,24 compared both Detached Eddy Simulation (DES) with Spalart-Allmaras (SA) and Large Eddy Simulation (LES) models with grid resolution following LES recommendations by Pope 25 with specific modifications made to the grid on HRM to avoid Grid Induced Separation (GIS).…”
Section: A the Generic Side View Mirrormentioning
confidence: 99%
“…At the BANC workshops in 2010 and 2012, various commercial Computational Fluid Dynamics (CFD) companies, government agencies, and academic institutions presented results. The tandem cylinder submissions to the first BANC workshop were summarized by David Lockard [2], and some groups published papers on their work [3,4,5,6]. Overall, it was found that despite the simple geometry, flow over tandem cylinders is challenging to model accurately, particularly due the boundary layer trip on the upstream cylinder [2].…”
Section: Introductionmentioning
confidence: 99%
“…In this particular case, the trip was located at an azimuthal angle of 55 • from the leading stagnation point. It resulted in experimental surface pressure profiles which were more representative of a Reynolds number above 4×10 6 , compared to a geometric Reynolds number of 1.66×10 5 [8], calculated using Eq. 1.…”
Section: Introductionmentioning
confidence: 99%
“…STAR CCM+ is a "classical" grid based CFD method widely utilized in the industry. It is viewed as one of the most advanced codes for predicting aeroacoustics, as seen in validation papers such as [67]. The question to be answered via this research was whether it is suitable for simulating propeller aeroacoustics in an efficient manner.…”
Section: Chapter 3: Numerical Methodsmentioning
confidence: 99%